Species-selective confinement of atoms dressed with multiple radiofrequencies. (18th April 2017) - Bentine, E; Harte, T L; Luksch, K; Barker, A J; Mur-Petit, J; Yuen, B; Foot, C J
Abstract: Methods to manipulate the individual constituents of an ultracold quantum gas mixture are essential tools for a number of applications, such as the direct quantum simulation of impurity physics. We investigate a scheme in which species-selective control is achieved using magnetic potentials dressed with multiple radiofrequencies, exploiting the different Landé g F -factors of the constituent atomic species. We describe a mixture dressed with two frequencies, where atoms are confined in harmonic potentials with a controllable degree of overlap between the two atomic species. This is then extended to a four radiofrequency scheme in which a double well potential for one species is overlaid with a single well for the other. The discussion is framed with parameters that are suitable for a 85 Rb and 87 Rb mixture, but is readily generalised to other combinations.